2016
DOI: 10.1002/adhm.201500878
|View full text |Cite
|
Sign up to set email alerts
|

Tunicate‐Inspired Gallic Acid/Metal Ion Complex for Instant and Efficient Treatment of Dentin Hypersensitivity

Abstract: Dentin hypersensitivity is sharp and unpleasant pains caused by exposed dentinal tubules when enamel outside of the tooth wears away. The occlusion of dentinal tubules via in situ remineralization of hydroxyapatite is the best method to alleviate the symptoms caused by dentin hypersensitivity. Commercially available dental desensitizers are generally effective only on a specific area and are relatively toxic, and their performance usually depends on the skill of the clinician. Here, a facile and efficient dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…The complex compound formation can involve both the carboxylate ion of GA and Ti-O − as donor groups. The formation of the coordination compound influences the chemical reactivity of polyphenols, for instance they are able to polymerize and to form coatings [56,57]: Particularly, in the present case it is shown that they were much more prone to be grafted on a surface. The possible formation of the complex and its binding to the surface is reported in Figure 2.…”
Section: Biomolecule Detectionmentioning
confidence: 60%
See 3 more Smart Citations
“…The complex compound formation can involve both the carboxylate ion of GA and Ti-O − as donor groups. The formation of the coordination compound influences the chemical reactivity of polyphenols, for instance they are able to polymerize and to form coatings [56,57]: Particularly, in the present case it is shown that they were much more prone to be grafted on a surface. The possible formation of the complex and its binding to the surface is reported in Figure 2.…”
Section: Biomolecule Detectionmentioning
confidence: 60%
“…A not negligible amount of calcium ion was detected on the samples functionalized in SBF (CT_GA_SBF_1, CT_GA_SBF_2) while negligible amount of calcium ion was observed on one sample functionalized in PBS (CT_GA_PBS_1): In this case, due to the very low amount and absence in PBS solution (at least theoretically), it can be considered a contamination. The presence of calcium on the samples incubated in the source solutions with SBF as medium, can be related to the GA ability to bind this element [8,30] within a complexation reaction [49,56]. It is reported [48,56] that polyphenols are prone to give complexation reactions in solutions containing metal ions; the structure of the coordination compounds can be different depending on the pH of the solution.…”
Section: Biomolecule Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tunicate, a marine invertebrate organism that encapsulates its body into a thick membrane called a tunic, exhibits a prominent self‐healing ability under seawater environment (≈8 pH) . Gallol‐functionalized 3,4,5‐trihydroxyphenylalanine (TOPA) plays an essential role in healing injuries, because gallol moieties in TOPA generate covalent cross‐linkage with functional groups and other proteins in the body of tunicate . Inspired by tunicate, tannic acid (TA), a representative gallol‐rich compound, was reported to be tethered to gelatin via Michael addition reaction under oxidizing conditions to produce biocompatible adhesives with intrinsic antibacterial ability .…”
Section: Introductionmentioning
confidence: 99%